2014
DOI: 10.1002/jemt.22394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic training, resistance training, or combined resistance-aerobic training on the left ventricular myocardium in a rat model

Abstract: This study follows the left ventricular (LV) hypertrophy in rats undergoing aerobic training alone (A), resistance training alone (R), or combined resistance and aerobic training (RA) (usually referred as concurrent training) program. A sedentary control group (C) was included. LV remodeling was evaluated using electron and light microscopy. The LV weight to body weight (LVW: BW) increased 11.4% in A group, 35% in the R group, and 18% in the RA group compared to the C group. The LV thickness increased 6% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
0
16
2
Order By: Relevance
“…In our study, that increased from 2.55% to 5.74%. Our collagen fraction values are not in accordance with those of the study by De Souza et al., 5 because the age and weight of the animals were different. However, other studies by our team with male Wistar rats of similar weights corroborate our findings, in which the collagen fraction varied from 2.5% to 3% in the control group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, that increased from 2.55% to 5.74%. Our collagen fraction values are not in accordance with those of the study by De Souza et al., 5 because the age and weight of the animals were different. However, other studies by our team with male Wistar rats of similar weights corroborate our findings, in which the collagen fraction varied from 2.5% to 3% in the control group.…”
Section: Discussioncontrasting
confidence: 99%
“… 12 , 13 That hypothesis is supported by a study showing an increase in interstitial collagen formation induced by aerobic training or RT. 4 The study by De Souza et al 5 has shown a 2.8% increase in the interstitial collagen fraction in the group submitted to RT (control group = 5.5% and trained group = 9%). In our study, that increased from 2.55% to 5.74%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, it is important to clarify that resistance strength training actually result in concentric cardiac hypertrophy, and a reduction in internal ventricular chamber dimensions (Barauna et al 2007, De Souza et al 2014). The resistance-trained heart is therefore morphologically similar to a heart with pressure overload-induced pathological hypertrophy, although the important distinction is that resistance training-induced hypertrophy does not result in cardiac dysfunction in healthy human subjects (Hurley et al 1984, Hagerman et al 2000).…”
Section: Physiological Hypertrophymentioning
confidence: 99%
“…Although these two types of exercise training have been studied extensively and their combination has been recently documented to promote health-related benefits in a wide range of populations [236], the effect of combined CVE and RE training on oxidative stress has been minimally studied.…”
Section: Combined Cve and Re Training And Oxidative Stressmentioning
confidence: 99%